Carrier dynamic and carrier Temperature in Quantum Well - Musa, Hiba J.; Flayyih, Ahmed H. (University of Thi-Qar Journal of Science, 2022)
Carrier temperature in quantum well (QW) semiconductor optical amplifier (SOA) has been studied, depending density matrix theory (DMT) and carrier dynamic in quantum well. The effect of volume carrier density, doping on effect, pulse shape, nonradiative relaxation, and nonlinear gain coefficients on the carrier temperature and carrier heating has been investigated. The theoretical results show that; the time recovery increases straightforward with nonradiative recombination, where the relaxation time of nonradiative recombination reduces the rate of carrier occupation in quantum states. Also, the carrier temperature increases with carrier density, free carrier absorption, carrier heating lifetime and reduces with pulse shape of pump pulses